Implementation of ADABOOST Algorithm on C50 for Improving the Performance of Liver Disease Classification - Anwar Sanusi; Chrystia Aji Putra; Fawwaz Ali Akbar (Fakultas Teknik Universitas Bhayangkara, 2023)
The liver is a vital organ that is important for humans because it plays a role in regulating hormone cycles, neutralizing toxins, and controlling the composition of blood. Liver disease is a common ailment worldwide. Often, this disease occurs without specific symptoms (asymptomatic). Therefore, liver disease is known as a